Pig with metal-hydride cathode under ion-stimulated desorbtion of hydrogen - Agarkov, A.V.; Ryabchikov, D.L.; Sereda, I.N.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2013)
The results of experimental investigation of penning type charged particles source with metal-hydride watercooled cathode are presented. The feature of investigation is hydrogen ion-stimulated desorbtion from metal-hydride as a way of working gas feeding. The influence of ion-stimulated desorbtion on emissive source characteristics was studied. In outflowing in axial direction charged particles flow the dynamic of energy distribution function of electrons and ions was carried out and their dependence on discharge external parameters was determined. Представлено результати експериментального дослідження джерела заряджених частинок пенінговського типу з металогідридним катодом, що охолоджується. Особливість дослідження полягає в способі напуску робочого газу за рахунок іон-стимульованої десорбції водню з металогідриду. Вивчено вплив іонстимульованої десорбції на емісійні характеристики джерела. У вихідному із джерела в аксіальному напрямку потоці заряджених часток досліджена динаміка функцій розподілу іонів й електронів по енергіях і визначена їхня залежність від зовнішніх параметрів розряду. Представлены результаты экспериментального исследования источника заряженных частиц пеннинговского типа с металлогидридным водоохлажденным катодом. Особенность исследования заключается в способе напуска рабочего газа за счет ион-стимулированной десорбции водорода из металлогидрида. Изучено влияние ион-стимулированной десорбции на эмиссионные характеристики источника. В выходящем из источника в аксиальном направлении потоке заряженных частиц исследована динамика функций распределения ионов и электронов по энергиям и определена их зависимость от внешних параметров разряда.